Etnonasionalisme pada Tradisi Serak gulo - Amanda Putri Pertiwi; Zaky Farid Luthfi; Rita Anggraini; Tetti Eka Purnama (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study aims to analyze the form of ethnonationalism reflected in the Serak gulo tradition among the Indian Muslim community in Padang Selatan District, as well as to identify obstacles and efforts in maintaining the Serak gulo tradition. The Serak gulo tradition is a local wisdom that not only has religious meaning but also serves as a form of gratitude and fulfillment of vows and strengthens social solidarity. This study uses a descriptive qualitative approach with a case study method. Data collection techniques were carried out through observation, in-depth interviews, and documentation with informants consisting of Indian Muslim community leaders, tradition practitioners and surrounding communities of different ethnicities. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using triangulation techniques to maintain data validity. The results of the study show that ethnonationalism in the Serak gulo tradition is reflected through the meaning, symbols, and stages of the tradition that emphasize the cultural identity of the Indian Muslim community. The stages of the tradition are carried out sequentially starting from collecting sugar, wrapping, reciting prayers, to the process of distributing sugar to the community. However, there are obstacles such as the distribution of sugar that is not carried out simultaneously, thus reducing the value of togetherness. Efforts made to maintain this tradition include hereditary preservation, strengthening the values ​​of togetherness, and active community involvement in every implementation.